Ganglioside complex antibodies in an Indian cohort of Guillain‐Barré syndrome. Issue 6 (29th September 2020) - Wahatule, Rahul; Dutta, Debprasad; Debnath, Monojit; Nagappa, Madhu; Mahadevan, Anita; Sinha, Sanjib; Sundaravadivel, Pandarisamy; Rao, Umamaheswara; Periyavan, Sundar; Binu, VS; Rao, Shivaji; Taly, Arun B
Abstract: Background: Antibodies against ganglioside complexes (GSCs) are associated with various clinical features and subtypes of Guillain‐Barré syndrome (GBS). Methods: One‐hundred patients were evaluated for antibodies to GSCs formed by combination of GM1, GM2, GD1a, GD1b, GT1b, and GQ1b using manual enzyme linked immuno‐sorbent assay (ELISA). Results: Twenty‐six patients were GSC antibody‐positive, most frequent being against GM1‐containing GSC (76.9%). Gender distribution, mean age, symptom‐duration, antecedent events, electrophysiological subtypes, requirement for mechanical ventilation, and median duration of hospital stay were comparable between the GSC antibody‐positive and negative groups. There was no association between specific GSC antibody and electrophysiological subtypes or clinical variants. After controlling for false discovery rate (FDR) using the Benjamini‐Hochberg method, the number of subjects who improved in overall disability sum score, modified Erasmus GBS outcome score, and neuropathy symptom score at discharge was significantly higher in the GSC antibody‐positive group. Improvements in Medical Research Council sum scores and Hughes Disability Scale during the hospital stay between the GSC antibody‐positive and negative groups were not significantly different after controlling for FDR. Conclusions: The GSC antibody‐positive group had better outcome at hospital discharge in some of the disability scores. Pathophysiological pathways among patients without GSC antibodies may be different and this requires further evaluation.